Variation in copper sensitivity between laboratory and wild strains of Caenorhabditis elegans. (January 2022) - Heaton, Andrew; Milligan, Emma; Faulconer, Elizabeth; Allen, Andrew; Nguyen, Timothy; Weir, Scott M.; Glaberman, Scott
Abstract: Ecological risk assessments of chemicals are frequently based on laboratory toxicity data from a small number of model species that may be reared in labs for years or decades. These populations can undergo many processes in the lab including artificial selection, founder effect, and genetic drift, and may not adequately represent their wild counterparts, potentially undermining the goal of protecting natural populations. Here we measure variation in lethality to copper chloride among strains of an emerging model species in toxicology, Caenorhabditis elegans . We tested four wild strains from Chile, Germany, Kenya, and Madeira (Portugal) against several versions of the standard laboratory N2 strain from Bristol, UK used in molecular biology. The four wild strains were more sensitive than any of the N2 strains tested with copper. We also found that the standard N2 strain cultured in the laboratory for >1 year was less sensitive than a recently cultured N2 strain as well as a cataloged ancestral version of the N2 strain. These results suggest that toxicologists should be cognizant of performing toxicity testing with long-held animal cultures, and should perhaps use multiple strains as well as renew cultures periodically in the laboratory. This study also shows that multi-strain toxicity testing with nematodes is highly achievable and useful for understanding variation in intra- and interspecific chemical sensitivity. Highlights: Multi-strain toxicity testing with nematodes is highly achievable. Mortality from copper chloride was evaluated in wild and standard N2 laboratory strains of Caenorhabditis elegans . Wild strains were similarly sensitive and were more sensitive to copper chloride than the laboratory N2 strains. Toxicologists should consider using multiple strains and renewing cultures when conducting toxicity testing with C. elegans .